2016
DOI: 10.1097/sla.0000000000001915
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictive Factors of Postprandial Hyperinsulinemic Hypoglycemia After Roux-en-Y Gastric Bypass

Abstract: The incidence of PHH significantly increased after RYGB but remained stable between 1 and 5 years. The estimation of beta-cell function with an OGTT before surgery can identify patients at risk for developing PHH after RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 42 publications
3
25
2
6
Order By: Relevance
“…The incidence of reactive hypoglycemia after RYGB is reported to be 9.1% 1 year after surgery and between 6.6% and 7.9% 5 years after RYGB [33,34]. However, some studies show reported symptoms without documented hypoglycemia [33], and others report documented low glucose values during an oral glucose tolerance test, but without concomitant symptoms [34]; therefore, the true prevalence of symptomatic hypoglycemia is difficult to establish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of reactive hypoglycemia after RYGB is reported to be 9.1% 1 year after surgery and between 6.6% and 7.9% 5 years after RYGB [33,34]. However, some studies show reported symptoms without documented hypoglycemia [33], and others report documented low glucose values during an oral glucose tolerance test, but without concomitant symptoms [34]; therefore, the true prevalence of symptomatic hypoglycemia is difficult to establish.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies show reported symptoms without documented hypoglycemia [33], and others report documented low glucose values during an oral glucose tolerance test, but without concomitant symptoms [34]; therefore, the true prevalence of symptomatic hypoglycemia is difficult to establish. In addition, there is overlap between symptoms of dumping and of hypoglycemia [33,34]. As hypothesized, large meals and liquid meals resulted in more frequent reactive hypoglycemia than smaller and/or meals of solid texture.…”
Section: Discussionmentioning
confidence: 99%
“…Nannipieri and colleagues (82) reported that preoperative BMI, fasting glucose, and nadir glucose during an oral glucose were lower, and insulin sensitivity and b-cell glucose sensitivity were higher in those who self-reported hypoglycemia symptoms and had low glucose values during oral GTT postoperatively. In another cohort, higher preoperative b-cell function predicted postoperative hypoglycemia (83). In both of these studies, measures of plasma glucose and b-cell function were derived from oral GTT postoperatively-a nonphysiologic and nonspecific test in this population.…”
Section: Prevalence Natural History and Risk Factorsmentioning
confidence: 99%
“…After ingestion of a glucose load, it is associated with an increased rate of intestinal glucose absorption peaking at 15e30 min, without evidence of glucose malabsorption [9,10]. This accelerated glucose absorption in turn triggers a markedly enhanced early postprandial plasma glucose and insulin responses, followed by the rapid clearance of plasma glucose and the occasional occurrence of postprandial hyperinsulinemic hypoglycemia [11,12]. Similar early postprandial absorption and increased postprandial clearance have been reported for fructose [13] or protein [14] as well.…”
Section: Discussionmentioning
confidence: 54%